Development and evaluation of a multi-media intervention to enhance the motor development of premature infants - Hughes, Anita J. (2017)
Background: Pregnancy is defined as lasting 40 weeks and birth that occurs before 37 weeks of gestation are classed as preterm, with neonates from as early as 22 weeks gestation surviving, although this is rare. Prematurity is associated with a range of long-term morbidities which negatively influence health and well-being. Infants born at less than 33 weeks gestation are at significantly increased risk for impaired motor development compared with their term peers (Allen, 2008). Deficits in motor skills such as balance, eye-hand co-ordination and manual dexterity have been well documented and are evident in infancy (Wood et al., 2000; Bracewell and Marlow, 2002). Early interventions have demonstrated some success in improving motor skills, but the effective elements were unclear. In addition, interactions between parent and infant can be problematic.